Tiam1-Rac Signaling Counteracts Eg5 during Bipolar Spindle Assembly to Facilitate Chromosome Congression - Woodcock, Simon A. (Cell Press, 2010)
Centrosome separation, critical for bipolar spindle formation and subsequent chromosome segregation during mitosis, occurs via distinct prophase and prometaphase pathways [1–3]. Kinesin-5 (Eg5), a microtubule (MT) motor, pushes centrosomes apart during bipolar spindle assembly [4]; its suppression results in monopolar spindles and mitotic arrest [5, 6]. Forces that antagonize Eg5 in prophase are unknown. Here we identify a new force generating mechanism mediated by the guanine nucleotide exchange factor (GEF) Tiam1, dependent on its ability to activate the GTPase Rac. We reveal that Tiam1 and Rac localize to centrosomes during prophase and prometaphase, and Tiam1, acting through Rac, ordinarily retards centrosome separation. Importantly, both Tiam1-depleted cells in culture and Rac1-deficient epithelial cells in vivo escape the mitotic arrest induced by Eg5 suppression. Moreover, Tiam1-depleted cells transit more slowly through prometaphase and display increased chromosome congression errors. Significantly, Eg5 suppression in Tiam1-depleted cells rectifies not only their increased centrosome separation but also their chromosome congression errors and mitotic delay. These findings identify Tiam1-Rac signaling as the first antagonist of centrosome separation during prophase, demonstrate its requirement in balancing Eg5-induced forces during bipolar spindle assembly in vitro and in vivo, and show that proper centrosome separation in prophase facilitates subsequent chromosome congression.